1995
DOI: 10.1007/bf00570252
|View full text |Cite
|
Sign up to set email alerts
|

Late thalamic atrophy in infarction of the middle cerebral artery territory in neonates

Abstract: We report four cases of progressive thalamic atrophy following ipsilateral cerebral infarction in the territory of the middle cerebral artery in neonates, with prospective radiological and clinical follow-up. This type of atrophy appears within 6 months after the onset of cerebral infarction. In the short term, this atrophy has no action on sensory and memory function and/or on sensory evoked potentials. This atrophy is not the result of secondary ischemic neuronal damage. Judging from several other experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…A delayed presentation after the age of 2 months was observed in 40% to 65% of PAIS in previous studies. 2,10,11 The radiological presentation of PAIS in this cohort showed that most strokes (78%) were limited to the middle cerebral artery territory (with classical late thalamic atrophy 12 ). This finding is in keeping with other studies with corresponding rates of 74% or 89%.…”
Section: Discussionmentioning
confidence: 73%
“…A delayed presentation after the age of 2 months was observed in 40% to 65% of PAIS in previous studies. 2,10,11 The radiological presentation of PAIS in this cohort showed that most strokes (78%) were limited to the middle cerebral artery territory (with classical late thalamic atrophy 12 ). This finding is in keeping with other studies with corresponding rates of 74% or 89%.…”
Section: Discussionmentioning
confidence: 73%
“…Children with neonatal middle cerebral artery (MCA) territory infarction may develop thalamic atrophy, but whether this has long-term implications for sensory perception is unclear. 34 In a study of 12 children and young adults with unilateral perinatal stroke, 4 had abnormal somatosensoryevoked potentials, but these children were unable to cooperate for further evaluation of sensory function. 35 In a study of 16 school-aged children with perinatal stroke, 6 (28%) had impaired visual function.…”
Section: Residual Effects Of Perinatal Strokementioning
confidence: 99%
“…31 One confounder is the existence of trans-synaptic antero- and retrograde neuronal atrophy. Cortical infarction over an extensive frontoparietal area perfused by the middle cerebral artery will cause delayed thalamic atrophy30 and macroscopic ipsilateral atrophy of the corticospinal tract at brainstem level above the decussation 2732 Precise delineation of the original focus of damage may not be straightforward when reviewed subsequently.…”
Section: Discussionmentioning
confidence: 99%